Influence of Biomass Burning on Temporal and Diurnal Variations of Acidic Gases, Particulate Nitrate, and Sulfate in a Tropical Urban Atmosphere - Sailesh N. Behera; Rajasekhar Balasubramanian (Advances in Meteorology)
The present study investigated the temporal and diurnal distributions of atmospheric acidic gases (sulphur dioxide (SO2), nitrous acid (HONO), and nitric acid (HNO3)) and those of particulate nitrate (NO3-) and sulfate (SO42-) through a comprehensive field campaign during the largest smoke haze episode in Singapore, a representative country in Southeast Asia (SEA). To identify the atmospheric behavior of these pollutants during the smoke haze period, the data generated from the measurement campaign were divided into three distinct periods: prehaze, during haze, and posthaze periods. The 24 hr average data indicated that ambient SO2, HONO, and HNO3 during the smoke haze episodes increased by a factor ranging from 1.2 to 2.6 compared to those during the prehaze and posthaze periods. Similarly, in the case of particulates SO42- and NO3-, the factor ranged from 2.3 to 4.2. Backward air trajectories were constructed and used to find the sources of biomass burning to the recurring smoke haze in this region. The air trajectory analysis showed that the smoke haze episodes experienced in Singapore were influenced by transboundary air pollution, caused by severe biomass burning events in the islands of Indonesia.